CENPF as an independent prognostic and metastasis biomarker corresponding to CD4+ memory T cells in cutaneous melanoma. Issue 4 (1st March 2022) - Li, Mengzhi; Zhao, Jingling; Yang, Ronghua; Cai, Ruizhao; Liu, Xusheng; Xie, Julin; Shu, Bin; Qi, Shaohai
Abstract: Owing to recent advances in immunotherapies, the overall survival of patients with skin cutaneous melanoma (SKCM) has increased; however, the 5‐year survival rate of metastatic patients remains poor. Skin cutaneous melanoma—upregulated genes were screened via analysis of differentially expressed genes (GSE3189 and GSE46517), and metastasis‐related oncogenes were identified via weighted gene coexpression network analysis of the GSE46517 dataset. As confirmed by the Tumor Immune Estimation Resource, we found highly expressed centromere protein F (CENPF) in SKCM and its metastases. Immunostaining of human melanoma tissues demonstrated high CENPF expression. According to the Kaplan‐Meier survival curve log‐rank test, receiver‐operating characteristic curve, and univariate and multivariate analyses, the Cancer Genome Atlas (TCGA) database suggested CENPF be a typical independent predictor of SKCM. The CIBERSORT algorithm classified the types of the immune cells from GSE46517 and showed higher proportion of CD4+ memory‐activated T cells in metastatic melanoma. Single‐sample gene set enrichment analysis of TCGA data confirmed the correlation between CENPF and activated CD4+ T cells. Centromere protein F was positively correlated with tumor mutational burden and CD4+ memory T cell markers (interleukin [IL]‐23A, CD28, and CD62L), negatively associated with memory T cell maintenance factors (IL‐7 and IL‐15) by correlation analysis. Moreover, immunofluorescence showed high coexpression of CENPF and IL23A, CD4 in melanoma. Upregulated CENPF might lead to premature depletion of CD4+ memory T cells and immunosuppression. Nomogram indicated CENPF clinical predictive value for 1‐, 3‐, 5‐, and 7‐year melanoma overall survival. Therefore, CENPF plays a vital role in the progression and metastasis of melanoma and can be an effective therapeutic target. Abstract : The clinical significance of centromere protein F (CENPF) in advanced skin cutaneous melanoma (SKCM) patients was demonstrated by online databases, clinical specimens, and weighted gene coexpression network analysis (WGCNA) analysis. Analyzing the association between immune cell composition and clinical type based on the CIBERSORT algorithm, we found that CENPF was significantly associated with CD4+ memory‐activated T cells. Immunofluorescence confirmed the expression of CENPF and CD4 in human melanoma. This technique helps to prevent the influence of melanin pigmentation. Centromere protein F, related to CD4+ memory‐activated T cell infiltration, is a vital indicator of advanced cutaneous melanoma and is associated with SKCM metastasis. CENPF may be a novel prognostic and immunotherapeutic target.